Polygamy in Malaysia: Ensuring Settlement of the First Wife’s Matrimonial Property Before Registering a Subsequent Marriage - Mardhiah Mazlan; Md. Yunus Abd Aziz (USIM Press, 2024)
In Malaysia, the Islamic Family Law Enactments provide the legal framework for both husbands and wives to claim matrimonial property, with heirs also eligible to claim in accordance with Sharia if the rightful owner has passed away. Such claims may arise under three circumstances: death, divorce, or polygamy. In cases of polygamy, the first wife has the right to claim her share of matrimonial property from her husband. However, procedural challenges often prevent these claims from being effectively pursued, as the process requires the wife to attend court during a time of emotional strain. Consequently, many choose to forgo their rights to marital property. This study aims to examine the legal provisions governing matrimonial property claims in polygamous contexts and to analyze the adverse impacts when such claims remain unresolved. The study proposes procedural improvements to facilitate the settlement of the first wife’s matrimonial property rights before the husband registers a subsequent marriage, thereby offering a more supportive legal process for affected parties.